A Patient with Proopiomelanocortin Deficiency: An Increasingly Important Diagnosis to Make - GÜRAN, TÜLAY (GALENOS YAYINCILIK, 2018)
Proopiomelanocortin (POMC) deficiency is a rare monogenic disorder with early-onset obesity. Investigation of this entity have increased our insight into the important role of the leptin-melanocortin pathway in energy balance. Here, we present a patient with POMC deficiency due to a homozygous c.206delC mutation in the POMC gene. We discuss the pathogenesis of this condition with emphasis on the crosstalk between hypothalamic and peripheral signals in the development of obesity and the POMC-melanocortin 4 receptors system as a target for therapeutic intervention.
Keywords: Obesity; melanocortin 4 receptors; paediatric obesity; proopiomelanocortin deficiency; EARLY-ONSET OBESITY; POMC-NULL MUTATION; RED HAIR; HOMOZYGOUS MUTATION; PIGMENTATION; HUMANS; GENE; FEATURES; HORMONE; LEPTIN